2020
DOI: 10.21203/rs.3.rs-99482/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Forests Phenolic Compounds Instigate Cloud Precipitation

Abstract: BackgroundThe wind shakes trees fluttering their leaves generating heat within. Mechanosensing is a crucial process in regulating trees’ growth and development. Mechanical stresses generate internal and external signals in trees. The aim is to establish the myriad of communication signals between forests, their ecology, wind and the clouds. ResultsAs result of leaves’ flutter trees open their stomata releasing phenolic compounds into the atmosphere. These aerosols linger in the atmosphere till they collide wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Wind, as an environmental stressor, may promote plant growth and affect secondary metabolites. Wind promotes heat exchange, gas trade, and photosynthesis on plant leaves [38]. It was reported that leaf morphology is altered when plants are exposed to wind, increasing the total phenolics in the leaves [39].…”
Section: Discussionmentioning
confidence: 99%
“…Wind, as an environmental stressor, may promote plant growth and affect secondary metabolites. Wind promotes heat exchange, gas trade, and photosynthesis on plant leaves [38]. It was reported that leaf morphology is altered when plants are exposed to wind, increasing the total phenolics in the leaves [39].…”
Section: Discussionmentioning
confidence: 99%